Immunoprevalence to Six Waterborne Pathogens in Beachgoers at Boquerón Beach, Puerto Rico: Application of a Microsphere-Based Salivary Antibody Multiplex Immunoassay - Augustine, Swinburne A. J.; Simmons, Kaneatra J.; Eason, Tarsha N.; Curioso, Clarissa L.; Griffin, Shannon M.; Wade, Timothy J.; Dufour, Alfred; Fout, G. Shay; Grimm, Ann C.; Oshima, Kevin H.; Sams, Elizabeth A.; See, Mary Jean; et al. (Frontiers in Public Health, 2017)
Waterborne infectious diseases are a major public health concern worldwide. Few methods have been established that are capable of measuring human exposure to multiple waterborne pathogens simultaneously using non-invasive samples such as saliva. Most current methods measure exposure to only one pathogen at a time, require large volumes of individual samples collected using invasive procedures and are very labor intensive. In this paper, we applied a multiplex bead-based immunoassay capable of measuring IgG antibody responses to six waterborne pathogens simultaneously in human saliva to estimate immunoprevalence in beachgoers at Boquerón Beach, Puerto Rico. Further, we present approaches for determining cut-offs to assess immunoprevalence to the pathogens in the assay. For the six pathogens studied, our results show that IgG antibodies against antigens from noroviruses GI.I and GII.4 were more prevalent (60% and 51.6% respectively) than Helicobacter pylori (21.4%), hepatitis A virus (20.2%), Campylobacter jejuni (8.7%) and Toxoplasma gondii (8%) in the saliva of the study participants. The salivary antibody multiplex immunoassay can be used to examine immunoprevalence of specific pathogens in human populations.